Effects of Metformin on Reproductive, Endocrine, and Metabolic Characteristics of Female Offspring in a Rat Model of Letrozole-Induced Polycystic Ovarian Syndrome With Insulin Resistance - Xie, Yidong; Xiao, Li; Li, Shangwei (Frontiers in Endocrinology, 2021)
The beneficial effects of metformin, especially its capacity to ameliorate insulin resistance (IR) in polycystic ovary syndrome (PCOS), explains why it is widely prescribed. However, its effect on the offspring of patients with PCOS remains uncertain. This study investigated the impact of metformin treatment on the first- and second-generation female offspring born to letrozole-induced PCOS-IR rats. Forty-five female Wistar rats were implanted with continuous-release letrozole pellets or placebo and treated with metformin or vehicle control. Rats exposed to letrozole showed PCOS-like reproductive, endocrine, and metabolic phenotypes in contrast to the controls. Metformin significantly decreased the risk of body weight gain and increased INSR expression in F1 female offspring in PCOS-IR rats, contributing to the improvement in obesity, hyperinsulinemia, and IR. Decreased FSHR expression and increased LHCGR expression were observed in F1 female rats of the PCOS-IR and PCOS-IR+Metformin groups, suggesting that FSHR and LHCGR dysfunction might promote the development of PCOS. Nevertheless, we found no significant differences in INSR, FSHR, and LHCGR expression or other PCOS phenotypes in F2 female offspring of PCOS-IR rats. These findings indicated widespread reproductive, endocrine, and metabolic changes in the PCOS-IR rat model, but the PCOS phenotypes could not be stably inherited by the next generations. Metformin might have contributed to the improvement in obesity, hyperinsulinemia, and IR in F1 female offspring. The results of this study could be used as a theoretical basis in support of using metformin in the treatment of PCOS-IR patients.